Liquid composition, method for coating a substrate with such a liquid composition and coated substrate obtained from such a method
Patent Information
- Application Number
- CN202580020999.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-14
- Filing Date
- 2025-03-06
- Publication Date
- 2026-10-13
AI Technical Summary
然而,这种方法存在局限性,因为发现高含量的金属颗粒对涂层与基材的粘附性能有负面影响
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to a liquid composition. It also relates to a method of coating a substrate with this liquid composition. Furthermore, it relates to a coated substrate obtained by this method.
[0002] The liquid composition according to the invention is designed to be applied to a substrate in the form of a curable coating, thereby obtaining a coated substrate. Furthermore, in the context of the invention, the liquid composition is intended to form an electrostatic dissipative coating, which is a coating with electrostatic dissipative properties that allow (static) electricity to dissipate on the outer surface of the substrate coated with this coating composition. With this coating, the formation of any static electricity on the surface is mitigated to the extent that electrostatic discharge on the surface is minimized or even prevented. Mitigation of electrostatic discharge is generally a desirable property for coatings on any article, and is particularly desirable in electronic devices, where relatively large electrostatic discharges can affect and interfere with the function of the electronic device. Background Technology
[0003] Existing electrostatic dissipative coatings are typically based on polymer coating compositions in which metal particles are dispersed. Generally, the dissipative properties of the coating can be enhanced by increasing the metal particle content in the coating composition. However, this approach has limitations, as high metal particle content has been found to negatively impact the adhesion between the coating and the substrate. This negative impact is so severe that, in some cases, the coating may peel off from the substrate during durability testing. Furthermore, durability testing has shown that the overall structural integrity of the coating may also be compromised when using high metal particle content. Summary of the Invention
[0004] The present invention aims to overcome the above-mentioned disadvantages in part or in whole.
[0005] To achieve the above objectives, a first aspect of the present invention relates to providing a liquid composition comprising: Prepolymer compositions that can be cured into polymeric substances. X-doped diamond particles, wherein X represents one or more chemical elements selected from Groups 13, 14 and / or 15 of the periodic system, and X preferably includes at least boron; The particles are dispersed in the prepolymer composition. Furthermore, the liquid composition is adapted to be applied to a substrate in the form of a coating that can be cured by drying, thereby obtaining a coated substrate, and wherein the obtained cured coating contributes to the electrostatic dissipation properties of the coated substrate.
[0006] In the liquid composition according to the invention, X-doped diamond particles impart attractive electrostatic dissipation properties to the entire composition.
[0007] Furthermore, it was observed that when this composition was applied to a substrate in the form of a coating, it exhibited satisfactory adhesion to the substrate and good structural integrity.
[0008] For clarity, it should be noted that, in the context of this invention, compound X may also be referred to by the common term "dopant".
[0009] Furthermore, X-doped diamond particles may include or consist of particles of so-called co-doped diamond containing dopant X as defined above, as well as additional dopant selected from a chemical element of a different group than that defined for X.
[0010] The term "prepolymer composition" refers to a composition containing precursor molecules that polymerize with each other upon curing, thereby forming a polymeric compound composed of the polymerized precursor molecules. When the prepolymer composition has been cured, a polymeric substance is obtained, which comprises a polymeric compound composed of individual precursor molecules that have reacted with each other. The obtained polymeric substance may contain additional compounds different from the polymeric compound.
[0011] In addition, it should be noted that the coating has adhesive properties, which allow for satisfactory adhesion to the substrate and also allow for the adhesion of another second substrate to the upper side of the coating away from the first substrate, thereby adhering the two substrates together by means of the coating.
[0012] In the context of this invention, the electrostatic dissipation properties imparted by the coating can be represented by the characteristic of "electrical sheet resistance" (Rs), which is frequently used for thin layers with uniform thickness. A typical unit for sheet resistance is ohms per square meter (Ω²), or expressed in SI units as ohms per square meter (Ωm / m²). 2 ).
[0013] When the coating's Rs value is 10 6 Up to 10 10At a range of ohms / square, attractive coating dissipation properties are achieved. The desired range of sheet resistance has a lower and upper limit to ensure sufficient dissipation of electrostatic charge while preventing the dissipation effect from being too high, i.e., the dissipated current may be so large as to damage the coated substrate.
[0014] Preferably, the liquid composition contains 10 to 60 wt.% X-doped diamond particles, more preferably 20 to 50 wt.%, and most preferably 35 to 45 wt.%. Alternatively, the same preferred range of X-doped diamond particles applies to the prepolymer composition. Thus, sufficient electrostatic dissipation properties and adhesion of the coating can be obtained. Within these preferred ranges, relatively low concentrations of X-doped diamond particles in the coating are generally observed to enhance adhesion, while relatively high concentrations enhance the electrostatic dissipation properties of the coating.
[0015] Preferably, the X content in the X-doped diamond particles is at most 10,000 ppm, and more preferably in the range of 100-1000 ppm. Specifically, this content is expressed as the number of X atoms or dopant atoms per diamond atom in the X-doped diamond particles. A higher X content in the X-doped diamond particles contributes to the electrostatic dissipation properties of the liquid composition, particularly the coating. The X content in the X-doped diamond particles is preferably at most 10,000 ppm to maintain the crystal structure of the diamond, thereby preserving the mechanical strength of the X-doped diamond particles.
[0016] Preferably, the X-doped diamond particles are n-type semiconductors, p-type semiconductors, and / or metallic conductors. The n-type semiconductor preferably comprises chemical elements selected from Group 15 of the periodic table. In the n-type semiconductor, X in X-doped diamond preferably represents one or more of the following chemical elements: nitrogen (N), phosphorus (P), arsenic (As), antimony (Sb), and / or bismuth (Bi). The n-type semiconductor increases the number of electrons in the diamond crystal structure of the X-doped diamond particles, thereby improving the conductivity of the X-doped diamond particles. The p-type semiconductor preferably comprises chemical elements selected from Group 13 of the periodic table. In the p-type semiconductor, X in X-doped diamond preferably represents one or more of the following chemical elements: boron (B), aluminum (Al), and / or gallium (Ga). The p-type semiconductor reduces the number of electrons in the diamond crystal structure of the X-doped diamond particles. The p-type semiconductor includes holes in the diamond crystal structure of the X-doped diamond particles, which improves the conductivity of the X-doped diamond particles. In addition to chemical elements from Group 13 or Group 15, chemical elements from Group 14, such as silicon (Si), germanium (Ge), tin (Sn), and / or lead (Pb), can be included, which allows for the formation of p-type semiconductors, n-type semiconductors, or metallic conductors.
[0017] X-doped diamond particles are typically produced via chemical vapor deposition (CVD) or high-pressure high-temperature (HPHT) processing. By applying these techniques, the X content in the X-doped diamond particles is adjustable and / or controllable, and therefore the electrostatic dissipation properties imparted by the X-doped diamond particles are also adjustable and / or controllable. Furthermore, when X-doped diamond particles are produced via CVD or HPHT processing, the (crystal) size and morphology of the X-doped diamond particles are adjustable and / or controllable.
[0018] X preferably represents one or more of the following chemical elements: boron (B), phosphorus (P), nitrogen (N), and / or silicon (Si). As mentioned above, boron, phosphorus, and nitrogen provide semiconductor properties to X-doped diamond particles. Silicon optionally also provides semiconductor properties to X-doped diamond particles, thus contributing to the electrical conductivity of X-doped diamond particles.
[0019] Preferably, the X-doped diamond particles have a particle size in the sub-millimeter range, more preferably in the range of 1-1000 µm, and most preferably in the range of 1-300 µm. Optionally, the X-doped diamond particles have a particle size in the range of 1-105 µm. Within this sub-millimeter range, the X-doped diamond particles can be readily included in the prepolymer composition. The size of the X-doped diamond particles is preferably less than or equal to the thickness of the obtained cured coating, preferably such that the X-doped diamond particles are completely incorporated into the coating. X-doped diamond particles with relatively large particle sizes optionally provide higher mechanical strength than X-doped diamond particles with relatively small particle sizes. The X-doped diamond particles can have a non-uniform size distribution and, for example, consist of groups of particles falling into various sub-ranges of particle size, as long as these sub-ranges fall within the overall range described above. Additionally, it should be noted that, since the overall preferred particle size according to the invention is in the sub-millimeter range, all particles or a portion thereof can have an actual size in the sub-micrometer range, i.e., in the range of 0.001 µm to 1.0 µm (so-called nanoparticles).
[0020] Preferably, the X-doped diamond particles are uniformly dispersed in the prepolymer composition. More preferably, the X-doped diamond particles are uniformly distributed or uniformly dispersed in the obtained cured coating. This provides a coating that allows electrostatic energy to be dissipated uniformly and / or uniformly protects the coated substrate from electrostatic discharge. Alternatively, the X-doped diamond particles are not uniformly dispersed in the prepolymer composition.
[0021] Typically, X-doped diamond particles are dispersed in a prepolymer composition by incorporating them into the prepolymer composition under environmental conditions.
[0022] Preferably, the prepolymer composition comprises a polyurethane prepolymer and / or a multi-component prepolymer composition. Such prepolymer compositions have been found to be highly suitable for achieving the intended advantageous effects of the present invention as described above. For clarity, it should be noted that the polyurethane prepolymer contains precursor molecules of the polyurethane polymer, and these precursor molecules react with each other upon curing to form the polyurethane polymer.
[0023] In particular, the use of polyurethane prepolymers is attractive because polyurethane exhibits good adhesion to a wide range of materials. A further advantage is the good resistance of cured polyurethane compositions to high temperature and humidity exposure. Furthermore, polyurethane demonstrates good resistance to corrosive or aggressive fluids.
[0024] Polyurethane prepolymer compositions typically contain diluents, curing agents, and / or monomer precursors for the basic polyurethane polymer.
[0025] An example of a usable polyurethane prepolymer composition of the present invention is the commercially available product "Aerodur Clearcoat" manufactured by Akzo Nobel, "Naftoseal MC780" from BASF, or "PR 1440" from PPG.
[0026] The liquid composition is preferably a viscous liquid, wherein the viscosity depends primarily on the type and relative content of the compounds it contains.
[0027] The liquid composition according to the invention is preferably a solution or suspension. Solutions or suspensions suitable for use in the invention typically have a viscosity in the range of 0 to 100 mPa·s. The viscosity of the liquid composition can vary over a wide range and is selected such that the liquid composition is best suited for application to a substrate in the form of a coating. Solutions or suspensions are generally suitable for application to a substrate by spraying.
[0028] More preferably, the liquid composition according to the invention is a gel or paste. In this context, gels typically have a viscosity between 100 and 10,000 mPa·s, and pastes typically have a viscosity of 10,000 mPa·s and higher.
[0029] Preferably, the liquid composition contains a solvent in an amount sufficient to achieve the desired viscosity of the liquid composition. Typically, the solvent is evaporated during the curing of the liquid composition.
[0030] Preferably, in the liquid composition according to the invention, the cured coating is transparent or opaque. The choice of either type depends on the type of substrate or article to which it is applied and the intended use of the coated substrate.
[0031] According to a second aspect of the present invention, a method for coating a substrate with a liquid composition according to a first aspect of the present invention is provided, comprising the following steps: - Apply the liquid composition to the substrate in the form of a coating; - Dry the coating, allowing it to cure and resulting in a coated substrate; The cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate; preferably, the cured coating has a static dissipation capacity of 10... 6 Up to 10 10 Shear resistance in the range of ohms / square.
[0032] Preferably, in the method according to the invention, the liquid composition is applied to the substrate by spraying, particularly when the liquid composition is a solution or suspension. Alternatively, the liquid composition can also be applied to the substrate in the form of a solution or suspension by brushing or rolling.
[0033] Preferably, in the method according to the invention, the liquid composition is applied directly to the substrate, particularly when the liquid composition is a gel or paste. Such a gel or paste-like liquid composition may also be referred to as an adhesive or kit. This adhesive or kit can advantageously be applied as an adhesive layer between two adjacent substrates to be bonded together.
[0034] Preferably, in the method according to the invention, the coating is dried under ambient conditions, wherein optionally, the temperature during drying is raised to above 20°C by heating. In the context of the invention, ambient conditions mean ambient air at 20°C and atmospheric pressure. Optionally, the coating may be dried at elevated temperatures, for example by using a heater or blower, to accelerate the curing process of the coating.
[0035] Preferably, in the method according to the invention, the thickness of the cured coating on the substrate is in the range of 1-90 µm, more preferably 70-90 µm. It is preferred herein that the coating thickness is uniform throughout the entire layer.
[0036] As an alternative to the second aspect of the present invention, the present invention also covers a method for coating a substrate, comprising the following steps: - Apply the prepolymer composition to a substrate in the form of a coating; - Apply X-doped diamond particles to the outer surface of the coating, wherein X represents one or more chemical elements selected from Group 13, Group 14 and / or Group 15 of the periodic table, and preferably X includes at least boron; - Dry the coating, allowing it to cure and obtain a coated substrate; The cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate, preferably such that the cured coating has a static dissipation capacity of 10.6 Up to 10 10 Square sheet resistance in the range of ohms / square.
[0037] The prepolymer composition is preferably a solution or suspension, especially a solution or suspension with a viscosity between 0 and 100 mPa·s.
[0038] Preferably, the prepolymer composition is applied to the substrate by spraying, particularly when the liquid composition is a solution or suspension. Alternatively, the liquid composition, in the form of a solution or suspension, is applied to the substrate using a brush or roller.
[0039] In an alternative method according to the invention, it is preferable to disperse X-doped diamond particles on the outer surface of the prepolymer coating and adhere them to the prepolymer coating. More preferably, the X-doped diamond particles are uniformly dispersed on the outer surface of the prepolymer coating.
[0040] X-doped diamond particles can almost completely or only partially cover the outer surface of the prepolymer coating. The higher the amount of X-doped diamond particles on the outer surface of the coating, the higher the dissipation performance.
[0041] Typically, X-doped diamond particles are applied to the outer surface of the coating by spraying, for example using a flake buster or airbrush.
[0042] In the method according to the invention, preferably, 1 to 40 grams of X-doped diamond particles are present per square meter on the outer surface of the coating. This has been found to be very suitable for achieving an attractive sheet resistance of 10 for the cured coating. 6 Up to 10 10 Within the required range of ohms / square.
[0043] In the method according to the invention, the coating is preferably dried under ambient conditions, wherein the temperature during drying is optionally raised to above 20°C by heating. A heater or blower may be used to increase the temperature during drying.
[0044] According to a third aspect, the present invention relates to a coated substrate obtained by any of the methods described above according to the invention, wherein the cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate, preferably such that the outer surface of the coated substrate has a surface area of 10... 6 Up to 10 10 Sheet resistance (in squares) within the range of ohms / square.
[0045] In this article, the substrate to be coated is preferably the outer surface part of a vehicle (such as a car or an airplane) that moves in the air, or the outer surface part of a device (such as a component of a wind turbine) that partially moves in the air.
[0046] Alternatively, external surface components exposed to both air and fluid (such as electrophysiological catheters) can be advantageously coated with the coating according to the invention. Detailed Implementation
[0047] Example
[0048] Embodiments of the invention claimed in this application are described below.
[0049] 1. Preparation of liquid compositions
[0050] The following forms a liquid composition that conforms to the claimed invention: - AkzoNobel Aerodur Clearcoat UVR is used as a prepolymer composition; - Boron-doped diamond (BDD) particles were used as X-doped diamond particles. The BDD particles were mixed into the prepolymer composition at a concentration of about 40 wt.% of the prepolymer composition.
[0051] Two different liquid compositions were formed: i) The first batch, in which the BDD particle size is in the range of 1-3 µm; ii) The second batch, in which the BDD particle size is in the range of 44-53 µm.
[0052] 2. Apply the liquid composition to the substrate.
[0053] Each of the two liquid compositions described above is applied to the respective glass substrate by spraying. The thickness of the liquid composition on the glass surface is approximately 70-90 µm.
[0054] The liquid composition is dried under ambient conditions. A cured coating is then obtained that adheres to the glass substrate.
[0055] 3. Evaluation of the dissipation performance of the coated substrate
[0056] The electrostatic dissipation properties of the coated substrate obtained above were investigated by performing the following measurements.
[0057] According to Section 25.0 of RTCA / DO-160, the sheet resistance of each cured coating on the glass substrate is determined as follows.
[0058] The sheet resistance of the coating itself was determined using a four-probe method, in which four equidistant, collinear electrical probes were used under ambient conditions. The four probes were brought into contact with the coating, with a current (I) applied between the two outer probes and the voltage drop (ΔV) between the two inner probes measured. Measurements were performed while a maximum voltage of 100 V (DC) was applied under ambient conditions.
[0059] The sheet resistance (R) of each coating was then determined by applying the following formula. s ):
[0060] Table 1
[0061] The two Rs values mentioned above are averages determined based on five actual measurements. The determined Rs values indicate that the Rs values vary to some extent with variations in the specific BDD particle size used in the coating composition. Importantly, both coatings according to the invention have an attractive 10... 6 Up to 10 10 Rs value within the range of ohms / square.
[0062] Furthermore, both coatings have been shown to exhibit good adhesion and structural integrity during durability testing.
Claims
1. A liquid composition comprising: - Prepolymer compositions that can be cured into polymeric forms; - X-doped diamond particles, wherein X represents one or more chemical elements selected from Groups 13, 14 and / or 15 of the periodic table, and X preferably includes at least boron; The particles are dispersed in the prepolymer composition. Furthermore, the liquid composition is adapted to be applied to a substrate in the form of a coating that can be cured by drying, thereby obtaining a coated substrate, and wherein the obtained cured coating contributes to the electrostatic dissipation properties of the coated substrate.
2. The liquid composition according to claim 1, wherein, The liquid composition comprises 10 to 60 wt.% X-doped diamond particles, preferably 20 to 50 wt.%, and most preferably 35 to 45 wt.%; or 10 to 60 wt.% X-doped diamond particles dispersed in the prepolymer composition, preferably 20 to 50 wt.%, and most preferably 35 to 45 wt.%.
3. The liquid composition according to any one of the preceding claims, wherein, The X content in the X-doped diamond particles is at most 10,000 ppm, and preferably in the range of 100-1000 ppm.
4. The liquid composition according to any one of the preceding claims, wherein, The X-doped diamond particles are n-type semiconductors, p-type semiconductors, and / or metallic conductors.
5. The liquid composition according to any one of the preceding claims, wherein, X represents one or more of the following chemical elements: boron, phosphorus, nitrogen, and / or silicon.
6. The liquid composition according to any one of the preceding claims, wherein, The X-doped diamond particles have a particle size in the sub-millimeter range, preferably in the range of 1-1000 μm, and more preferably in the range of 1-300 μm.
7. The liquid composition according to any one of the preceding claims, wherein, The X-doped diamond particles are uniformly dispersed in the prepolymer composition.
8. The liquid composition according to any one of the preceding claims, wherein, The prepolymer composition comprises a polyurethane prepolymer and / or a multicomponent prepolymer composition.
9. The liquid composition according to any one of the preceding claims, wherein, The liquid composition is a solution or suspension.
10. The liquid composition according to any one of the preceding claims, wherein, The liquid composition is a gel, or wherein the liquid composition is a paste.
11. The liquid composition according to any one of the preceding claims, comprising a solvent in an amount sufficient to achieve the desired viscosity of the liquid composition.
12. The liquid composition according to any one of the preceding claims, wherein, The cured coating may be transparent or opaque.
13. A method for coating a substrate with a liquid composition according to any one of claims 1-12, comprising the following steps: - Apply the liquid composition to a substrate in the form of a coating; - Dry the coating to cure it and obtain a coated substrate; The cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate; preferably, the cured coating has a static dissipation capacity of 10... 6 Up to 10 10 Shear resistance in the range of ohms / square.
14. The method according to claim 13, wherein, The liquid composition is applied to the substrate by spraying, particularly when the liquid composition is a solution or suspension.
15. The method according to any one of claims 13 to 14, wherein, The liquid composition is applied directly to the substrate, especially when the liquid composition is a gel or paste.
16. The method according to any one of claims 13 to 15, wherein, The coating is dried under ambient conditions, wherein, optionally, the temperature during drying is raised to above 20°C by heating.
17. The method according to any one of claims 13 to 16, wherein, The cured coating on the substrate has a thickness in the range of 1-90 μm, preferably 70-90 μm.
18. A method for coating a substrate, comprising the following steps: - Apply the prepolymer composition to the substrate in the form of a coating; - Apply X-doped diamond particles to the outer surface of the coating, wherein X represents one or more chemical elements selected from Groups 13, 14 and / or 15 of the periodic table, and preferably X includes at least boron; - Dry the coating to cure it and obtain a coated substrate; The cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate; preferably, the cured coating has a static dissipation capacity of 10... 6 Up to 10 10 Sheet resistance (in squares) within the range of ohms / square.
19. The method according to claim 18, wherein, The X-doped diamond particles are dispersed on the outer surface of the prepolymer coating and adhere to the prepolymer coating.
20. The method according to any one of claims 18 to 19, wherein, On the outer surface of the coating, there are 1 to 40 grams of X-doped diamond particles per square meter.
21. The method according to any one of claims 18 to 20, wherein, The coating is dried under ambient conditions, wherein, optionally, the temperature during drying is raised to above 20°C by heating.
22. A coated substrate, obtained by the method according to any one of claims 13 to 17 or the method according to any one of claims 18 to 21, wherein, The cured coating adheres to the substrate and contributes to the electrostatic dissipation properties of the coated substrate, preferably such that the outer surface of the coated substrate has a static dissipation capacity of 10. 6 Up to 10 10 Sheet resistance (in squares) within the range of ohms / square.
23. The coated substrate according to claim 22, wherein, The substrate is an outer surface component of a vehicle that moves in the air, such as a car or an airplane; or an outer surface component of a device that partially moves in the air, such as a component of a wind turbine.